2016
DOI: 10.4103/0971-9261.182588
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of quality of life of operated cases of esophageal atresia in the community

Abstract: Aims:To evaluate the outcome of the operated children of esophageal atresia (EA) focusing on their early and late morbidity and mortality and quality of life (QoL) of survivors.Settings and Design:A cross-sectional follow-up with retrospective analysis of available medical and surgical records of children who underwent repair for EA.Materials and Methods:The medical records of the children who underwent repair for EA during the period from 2000 to 2011 at the Christian Medical College Hospital, Vellore, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
3
11
1
Order By: Relevance
“…The EA with or without TEF is the common congenital anomaly found in isolation or in combination with other associated anomalies in neonates that affect them later in their childhood even after the definite repair. These children tend to have ongoing illnesses due to numerous complications which contribute to higher incidence of impaired physical functioning as reported by Leibovitch et al, 4 Menzies et al, 5 Bal et al, 22 Lacher et al, 23 and Seo et al 24 Similar results were observed in the present study as almost half of children had low weight and height for age. Surgery done in the neonatal period under general anesthesia, prolonged ventilation, and development of early and late complications in childhood requiring repeated hospitalization is considered to be the contributing factors for delayed neurodevelopment among these children.…”
Section: Discussionsupporting
confidence: 89%
“…The EA with or without TEF is the common congenital anomaly found in isolation or in combination with other associated anomalies in neonates that affect them later in their childhood even after the definite repair. These children tend to have ongoing illnesses due to numerous complications which contribute to higher incidence of impaired physical functioning as reported by Leibovitch et al, 4 Menzies et al, 5 Bal et al, 22 Lacher et al, 23 and Seo et al 24 Similar results were observed in the present study as almost half of children had low weight and height for age. Surgery done in the neonatal period under general anesthesia, prolonged ventilation, and development of early and late complications in childhood requiring repeated hospitalization is considered to be the contributing factors for delayed neurodevelopment among these children.…”
Section: Discussionsupporting
confidence: 89%
“…The main postoperative complications among the 13 survived neonates included pneumonia, wound infection, anastomotic leak, gastroesophageal reflux and stricture formation were comparable to previous studies (Brown and Tam 1996;Mansur et al, 2005) as these postoperative outcomes are mainly reported in cases with EA with or without TEF. From other point of view, the complications were more frequent with the wider gap, more than 3 cm, these findings supported that reported by Mansur et al, (Mansur et al, 2005) from Egypt and other earlier studies (Bal et al, 2016;Brown and Tam 1996;Livitidis 1973;Puri et al, 1981). The current study suggested that the length of the gap could be a good predictor for the outcome of neonates with EA/TEF, however further studies and further investigations are necessary to explicit the definite predictive role.…”
Section: Resultssupporting
confidence: 91%
“…According to our findings females were the dominantly affected with EA/TEF compared to male neonates, while no such difference in survival between both genders, Bal et al, (Bal et al, 2016) found relatively higher incidence among males with a male to female ratio of 41:39, with no significant difference between both genders neither in incidence nor survival, despite the higher incidence in females in our study no significant difference between both genders in survival. Table.3 Gap length of EA/TEF neonates Table.4 Post-operative complications among the 13 survived EA/TEF neonates* *Some cases had more than one complication at the same time Table.5 Distribution of mortality and survival according to the gap length Table.6 Distribution of postoperative complications according to the gap length of survived neonates (N =13)* *Some cases had more than one complication at the same time Associated anomalies and comorbidities were reported in 10/25 (40%) neonates, which is comparable to that reported by Stoll et al, (Stoll et al, 2009) and.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…described HRQoL among children and adolescents born with EA, [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] three of which 32,34,38 also reported on HRQoL among adults (patients >18 years old). The remaining two articles described HRQoL among adults with EA only.…”
Section: Current Literature Regarding Hrqol In Patients Following Ea mentioning
confidence: 99%